Hubungan Antara Tingkat Stres dengan Status Gizi pada Mahasiswa Akhir Fakultas Kedokteran Universitas Lampung - Zefanya Angie; Reni Zuraida; Ramadhana Komala; Bayu Anggileo Pramesona (Lembaga Pengembangan Kinerja Dosen, 2025)
Stress is a psychological condition that can affect nutritional status through changes in eating patterns and body metabolism. This study aimed to analyze the relationship between stress levels and nutritional status among final-year medical students at the Faculty of Medicine, University of Lampung. The study was conducted from November 2024 to January 2025 using a cross-sectional approach. The population consisted of final-year medical students in the 2024 academic year. A total of 141 students were selected using a simple random sampling technique. Data analysis was performed using the gamma correlation test. Stress levels were assessed using the Medical Student Stressor Questionnaire (MSSQ), while nutritional status was measured through anthropometric assessments. The results showed that 34.8% of respondents had an overweight or obese nutritional status, and 44.7% experienced moderate stress levels. Bivariate analysis revealed a significant relationship between stress levels and nutritional status (p = 0.033, p < 0.05) with a weak positive correlation (r = 0.260). This positive correlation indicates that higher stress levels are associated with an increased risk of being overweight or obese. In conclusion, this study demonstrates a significant relationship between stress levels and nutritional status among final-year medical students. These findings highlight the importance of effective stress management to prevent the risk of excessive weight gain and its potential contribution to degenerative diseases.